Control of Adipocyte Thermogenesis and Lipogenesis through β3-Adrenergic and Thyroid Hormone Signal Integration - Guilherme, Adilson; Yenilmez, Batuhan; Bedard, Alexander H; Henriques, Felipe; Liu, Dianxin; Lee, Alexandra; Goldstein, Lauren; Kelly, Mark; Nicoloro, Sarah M; Chen, Min; Weinstein, Lee; Collins, Sheila; et al. (Cell reports, 2020)
Here, we show that β adrenergic signaling coordinately upregulates de novo lipogenesis (DNL) and thermogenesis in subcutaneous white adipose tissue (sWAT), and both effects are blocked in mice lacking the cAMP-generating G protein-coupled receptor Gs (Adipo-GsαKO) in adipocytes. However, UCP1 expression but not DNL activation requires rapamycin-sensitive mTORC1. Furthermore, β3-adrenergic agonist CL316243 readily upregulates thermogenic but not lipogenic genes in cultured adipocytes, indicating that additional regulators must operate on DNL in sWAT in vivo. We identify one such factor as thyroid hormone T3, which is elevated locally by adrenergic signaling. T3 administration to wild-type mice enhances both thermogenesis and DNL in sWAT. Mechanistically, T3 action on UCP1 expression in sWAT depends upon cAMP and is blocked in Adipo-GsαKO mice even as elevated DNL persists. Thus, T3 enhances sWAT thermogenesis by amplifying cAMP signaling, while its control of adipocyte DNL can be mediated independently of both cAMP and rapamycin-sensitive mTORC1.
Keywords: Animals; myši transgenní; Adipose Tissue, Brown; hnědá tuková tkáň; lipogeneze; termogeneze; Adipose Tissue, White; Mice, Transgenic; Adrenergic Agents; Adipocytes; signální transdukce; Signal Transduction; Thermogenesis; Thyroid Hormones; hormony štítné žlázy; Lipogenesis; zvířata; bílá tuková tkáň; adrenergní látky; tukové buňky